2021
DOI: 10.1093/cercor/bhab222
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Continuous Theta Burst Stimulation Facilitates Auditory–Vocal Integration in Spinocerebellar Ataxia

Abstract: Clinical studies have shown the efficacy of transcranial magnetic stimulation in treating movement disorders in patients with spinocerebellar ataxia (SCA). However, whether similar effects occur for their speech motor disorders remains largely unknown. The present event-related potential study investigated whether and how abnormalities in auditory–vocal integration associated with SCA can be modulated by neuronavigated continuous theta burst stimulation (c-TBS) over the right cerebellum. After receiving active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 74 publications
2
22
0
Order By: Relevance
“…Moreover, not all behavioral and neural responses were modulated in the same direction: following c-TBS over the left SMA, 78–84% of vocal, P1, and P2 responses were reduced and 72% of N1 responses were enhanced, while the others showed the opposite pattern (see Figure 3 ). Such inter-individual variability has also been reported in previous empirical and clinical studies that investigated the TMS effects on motor and cognitive behaviors ( Lopez-Alonso et al, 2014 ; Corp et al, 2020 ; Lin et al, 2022 ), depending on many factors such as stimulation protocol, brain structure, hormonal levels, and genetic polymorphisms ( Polania et al, 2018 ). Addressing inter-individual variability of TMS effects has crucial implications for improving the efficacy of this non-invasive brain stimulation approach for the treatment of motor speech disorders in PD.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, not all behavioral and neural responses were modulated in the same direction: following c-TBS over the left SMA, 78–84% of vocal, P1, and P2 responses were reduced and 72% of N1 responses were enhanced, while the others showed the opposite pattern (see Figure 3 ). Such inter-individual variability has also been reported in previous empirical and clinical studies that investigated the TMS effects on motor and cognitive behaviors ( Lopez-Alonso et al, 2014 ; Corp et al, 2020 ; Lin et al, 2022 ), depending on many factors such as stimulation protocol, brain structure, hormonal levels, and genetic polymorphisms ( Polania et al, 2018 ). Addressing inter-individual variability of TMS effects has crucial implications for improving the efficacy of this non-invasive brain stimulation approach for the treatment of motor speech disorders in PD.…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, Sebastian et al (2020) found greater beneficial effects on naming functions (relative to sham) when chronic post-stroke patients received cathodal tDCS over the right cerebellum than when they received anodal cerebellar tDCS. And applying inhibitory cTBS over the right cerebellum led to facilitatory effects on impaired vocal motor control in patients with SCA ( Lin et al, 2022 ). As compared to rTMS, cTBS induces robust, long-lasting changes in activation in much shorter periods.…”
Section: Discussionmentioning
confidence: 99%
“…The reported average depth of the lateral cerebellar gray matter is approximately 14.6–14.7 mm from the scalp surface, which is within a range of ∼30 mm at 100% peak output of the figure-of-8 coil ( Hardwick et al, 2014 ). Several studies have successfully applied rTMS or TBS over the cerebellum with a figure-of-8 coil to change motor or speech performance ( Theoret et al, 2001 ; Koch et al, 2008 ; Popa et al, 2010 ; Demirtas-Tatlidede et al, 2011 ; Lin et al, 2022 ). On the other hand, the present study protocol performs acoustic signal analysis to extract speech parameters for the evaluation of language function with the WAB, BDAE, and BNT scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations